Entrepreneurial Orientation Among Migrants and Small and Medium Enterprises - Omisakin, O; Nakhid, C; Littrell, R; Verbitsky, J (Sciedu Press, 2016)
This qualitative study seeks to enrich the understanding of migrants’ perceived experience in running small businesses in Auckland, New Zealand. The study will also examine what motivated migrants into business, their experiences in labour market as well as the challenges they faced in running a business. The study focuses on African migrant small business owners excluding South Africans as this population has been extensively researched and documented (Meares et al., 2011; Warren, 2003). The theoretical foundation of the study rests on labour disadvantage and cultural theories. In-depth open ended face-to face interviews between 11-20 participants selected through purposive sampling will be used to collect data. Thematic analysis will be used to analyse data collected.
Keywords: Migrants; Migrant enterprises; Migrant entrepreneur; Entrepreneurship; Environment; Business performance